Point of choice kilocalorie labelling in the UK eating out of home sector: a descriptive study of major chains - Eric Robinson; Sam Burton; Tom Gough; Andrew Jones; Ashleigh Haynes (BMC, 2019)
Abstract Background Eating out is now common and food served out of the home is often of low nutritional quality. Kilocalorie (kcal) labelling of food and drink products sold in restaurant chains in the US is now mandatory, although in store kcal labelling practices among major UK restaurant and takeaway chains have not been examined. Methods During August 2018, we contacted, visited the website and/or retail outlets of major eating out and takeaway food chains in the UK, including full-service and fast-food restaurants, cafes and coffee shops, some of which had previously made a voluntary pledge to provide kcal labelling. We examined the proportion of chains providing kcal information to customers at point of choice in store and the extent to which kcal information provision adhered to labelling recommendations. We also examined the proportion of chains that did not have point of choice kcal labelling but were able to provide kcal information on request. The study protocol was pre-registered on the Open Science Framework. Results Of the 104 eligible chains, only a small minority (18 chains, 17%) provided in store kcal labelling. Of those that did, provision of kcal information tended not to adhere to recommended labelling practices. Of the 16 eligible chains that had previously committed to a voluntary public health pledge to provide point of choice kcal labelling, labelling did not meet recommendations and 4 (25%) did not provide kcal labelling. Of the 86 chains that did not provide kcal labelling in store, kcal information was available on request from 43 (50%) chains. Conclusions It is rare for eating out and takeaway chains in the UK to provide point of choice kcal labelling and when labelling is provided it does not adhere to recommended labelling practices. Chains that previously volunteered to provide kcal labelling as part of an industry and public health partnership do so inadequately. Voluntary policies have not resulted in adequate kcal labelling in the UK eating out of home sector.